(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The pheromonal and kairomonal activity of the P. citri sex pheromone and of three analogs: methyl-ester, ethylidene analog (E/Z mixture) and homolog were studied. Traps baited with these compounds as well as traps baited with the pheromone + 10% of its alcohol were exposed in Italy and Israel in avocado, persimmon and citrus orchards from August to October 1999 and in June and August 2000. Control traps were baited with dispensers loaded with hexane used as solvent for the pheromone and its analogs. The highest captures of males were obtained with the sex pheromone. Addition of 10% of the corresponding alcohol to the sex pheromone did not affect the level of trapping. The methyl-ester showed no activity while the ethylidene analog displayed moderate activity. It caught considerable numbers of males, but significantly less than the sex pheromone. The homolog displayed strong activity, which was the same as the pheromone in some of the tests. Since its synthesis is easier and cheaper than that of the pheromone, it may replace the pheromone in field-work. Captures of natural enemies was not recorded in Israel and in Italy. Only a few specimens of the encyrtid Anagyrus pseudococci have been captured in pheromone baited and in the control traps, in spite of the fact that the parasitoid as well as other natural enemies of the mealybug were abundant at the time of the field tests. These findings indicate that the studied compounds are not kairomones.